Achieving the 2025 World Health Assembly targets for nutrition in India: What will it cost? - Chakrabarti, Suman; Kapur, Avani; Vaid, Abhilasha; Menon, Purnima (International Food Policy Research Institute, 2017)
Our analysis indicates that there are large interstate differences in the delivery of essential nutrition interventions across India, and considerable variability in the estimated costs of delivering these interventions at scale. Additionally, allocations to key ministries, such as the MoHFW and the MoWCD, for nutrition, have been stagnant or have declined over the years. Furthermore, budget allocations for critical public health interventions such as toilets and piped water, are still quite low and will likely be inadequate to cover all families.